Apoyo familiar en la atención de niños con problemas de aprendizaje en el área de matemáticas - Bajaña Salazar, Herminia Haydeé (2021)
Currently, learning problems have become a critical point in basic primary and high school education, even though in developed countries this type of problem has been investigated since the 60s of the past century in Latin America this issue at the school level is relatively recent. Among the learning problems the best known is dyslexia, but there are also disorders in the area of mathematics, specifically dyscalculia, which is not generally known, research indicates that the vast majority of people who suffer it are not diagnosed. Regarding the family environment, many parents are unaware that their children suffer from some type of learning difficulties, since many of them do not present obvious signs, this hinders the development of the child since an early intervention has a beneficial impact on the cognitive development of the child........